The Effect of Using Fermented Maggot Flour on The Growth of Tilapia Fish (Oreochromis niloticus) - Taslim, Muhammad; Lestari, Dewi Putri; Rahmadani, Thoy Batun Citra (Jurnal Biologi Tropis, 2025)
Tilapia (Oreochromis niloticus) is one of the freshwater commodities that is most in demand by local and foreign commonities. The increasing price of fish feed has resulted in decreasing income for farmers. One of the feeds that has a high protein content is maggot. One of the procesing technologies to reduce fat content in maggots is by using fermentation technology. Thus, the purpose of this study is to ascertain the impact of fermented maggot flour on the growth of tilapia (Oreochromis niloticus). The experimental design used in this study was a Completely Randomized Design (CRD), with six treatments and three replications, resulting in the production of 18 experimental units: P0 (commercial feed 100), P1 (commercial feed 25% + 75% non-fermented maggot flour), P2 (commercial feed 25% + 75% fermented maggot flour), P3 (commercial feed 75% + 25% non-fermented maggot flour), P4 (commercial feed 75% + fermented maggot flour), and P5 (100% fermented maggot). The addition of maggot flour and maggot fermented flour with different doses, the best treatmens was obtained in P2 (commercial feed 25% + 75% fermented maggot flour). Treatment  P2 could increase the absolute weight growth rate, SGR,EPP, and produced the lowest FCR. However, the addition of maggot flour and maggot fermentation was not significant on absolute lenght growth, feed consumtion level, SR. Thus, the optimal concentration of maggot flour and maggot fermentation in this study was 75% maggot fermentation flour + 25% commercial feed.